On Fertile Ground: Locating Historic Sites in the Landscapes of Fundy and the Foothills - Campbell, Claire (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractSince the 1972 National Museums Policy announced its goals of “democratization and decentralization,” national historic sites have been marked by a trend toward regionalization. While scholars have focused on the nationalizing impetus of twentieth-century historiography before 1970, subsequently there have been consistent efforts to incorporate local environmental and cultural diversity into the “family” of national sites. This paper demonstrates this system-wide trend by comparing historic sites in the Bay of Fundy and the Alberta foothills. In both places, designation has evolved from the two-nations narrative of French-English rivalry, in seventeenth-century forts or fur trade posts which could integrate far-flung localities, thereby claiming transcontinental space as national territory. Interpretation now credits local ecological factors with shaping the course of historical events, and acknowledges in situ resources. In addition, Parks Canada has involved groups such as the Acadians or the Blackfoot, whose claims of “homeland” jostle the naturalized Canadian boundaries affirmed by the older national narrative. There are other complications, raised by revisions in public history; notably, these sites continue to play a role in the marketing of place – in a long tradition of using the landscape as an entrée to tourism – and they are not yet conceived in regional groupings.